Climate Smart Village Project: How to use the leaf color chart (Bihar, India) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) (www.ccafs.cgiar.org) has introduced the model of "Climate Smart Villages (CSVs)" in India, and is slowly scaling up and expanding to other countries in the South Asia region. The idea is to raise awareness among farming communities in South Asia about various technological, institutional and policy-oriented options that have the potential to increase their climatic resilience, adapt to climate change, increase agricultural productivity and income, while reducing emissions of greenhouse gases. In this video, you will learn more about the benefits from using a leaf colour chart, which indicates how much fertilizers should be used in the field depending on the colour of the leaves. Read more: http://ow.ly/kXVFR